BILATERAL ACUTE ENDOPHTHALMITIS ASSOCIATED WITH MUNCHAUSEN SYNDROME. Issue Volume 9:Issues 2(2015:Spring) (2015) - Rao, Prethy; Shah, Ankoor R.; Michelotti, Monica M.; Anderson, Bradley; Abbey, Ashkan M.; Jain, Nieraj; Stec, Lori; Lowe, Lori; Johnson, Mark W.; Williams, George A.
Abstract : Purpose: Endophthalmitis is a potentially blinding intraocular infection that requires urgent intervention. Self-inflicted endophthalmitis is rare, difficult to diagnose, and requires a multidisciplinary approach for management. The purpose is to present a rare case of sequential self-inflicted acute endophthalmitis as a feature of Munchausen syndrome. Methods: This is a case report reviewing imaging and laboratory studies. Results: A 42-year-old female patient developed culture-proven acute endophthalmitis sequentially in both eyes with different bacterial strains. There was clear evidence of self-inflicted corneal puncture tracks in the right eye, and during the course of inpatient psychiatric evaluation, the patient admitted to self-inflicted ocular perforations. Conclusion: Patients with Munchausen syndrome often injure themselves as a method of drawing attention, sympathy, or reassurance. Although ocular injuries due to psychiatric disease are known to occur, intraocular injection as a mode of self-injury is extremely rare. A high index of suspicion must be maintained when the reported history and clinical course are inconsistent. Abstract : Patients with Munchausen syndrome often injure themselves as a method of drawing attention, sympathy, or reassurance. Although ocular injuries due to psychiatric disease are known to occur, intraocular injection as a mode of self-injury is extremely rare. A high index of suspicion must be maintained when the reported history and clinical course are inconsistent.